Development of modular school design as a permanent solution for post-disaster reconstruction in Indonesia. Issue 1 (7th September 2020) - Yatmo, Yandi Andri; Atmodiwirjo, Paramita; Saginatari, Diandra Pandu; Harahap, Mochammad Mirza Yusuf
Abstract : Purpose: This paper describes the development and implementation of a modular school building design prototype to support "build back better" after the disaster. The purpose of this paper is to bridge the gap between the two standard practices of post-disaster reconstruction: the quickly temporary construction and the permanent solution with longer time to complete. Design/methodology/approach: The modular school design prototype was developed based on three design criteria established to achieve a relatively quick construction with good quality as a post-disaster permanent solution. The prototype was implemented in Kerandangan Village, Lombok and evaluated to review its compliance with the design criteria. Findings: Three design strategies were proposed to respond to the main design criteria: the use of modular units and components, the material durability and availability, and the "plug-and-play" configuration system. Through these strategies, the prototype demonstrated the ability to perform as a permanent solution to be implemented in a short time. The prototype evaluation suggests some possible improvement to ensure a more efficient process and further replicability. Originality/value: The development of the modular design bridges the gap between temporary and permanent approach for post-disaster school reconstruction. The highlighted criteria and the proposed design strategies contribute to the "build back better" attempt by providing better learning experiences for children through a replicable modular design that could be flexibly adapted to various local contexts.